The Effects of Two Different Ankle-Foot Orthoses on Gait of Patients with Acute Hemiparetic Cerebrovascular Accident. (9th September 2014) - Rao, Noel; Wening, Jason; Hasso, Daniel; Gnanapragasam, Gnanapradeep; Perera, Priyan; Srigiriraju, Padma; Aruin, Alexander S.
Abstract : Objective . To compare the effects of two types of ankle-foot orthoses on gait of patients with cerebrovascular accident (CVA) and to evaluate their preference in using each AFO type. Design . Thirty individuals with acute hemiparetic CVA were tested without an AFO, with an off-the-shelf carbon AFO (C-AFO), and with a custom plastic AFO (P-AFO) in random order at the time of initial orthotic fitting. Gait velocity, cadence, stride length, and step length were collected using an electronic walkway and the subjects were surveyed about their perceptions of each device. Results . Subjects walked significantly faster, with a higher cadence, longer stride, and step lengths, when using either the P-AFO or the C-AFO as compared to no AFO (P < 0.05 ). No significant difference was observed between gait parameters of the two AFOs. However, the subjects demonstrated a statistically significant preference of using P-AFO in relation to their balance, confidence, and sense of safety during ambulation (P < 0.05 ). Moreover, if they had a choice, 50.87 ± 14.7 % of the participants preferred the P-AFO and23.56 ± 9.70 % preferred the C-AFO. Conclusions . AFO use significantly improved gait in patients with acute CVA. The majority of users preferred the P-AFO over the Cf-AFO especially when asked about balance and sense of safety.